2016
DOI: 10.18295/squmj.2016.16.02.010
|View full text |Cite|
|
Sign up to set email alerts
|

Spousal Concordance of Diabetes Mellitus among Women in Ajman, United Arab Emirates

Abstract: There was significant concordance of abnormal glycaemia among non-diabetic women with diabetic husbands. The spouses of diabetic patients may therefore be a target population for regular hyperglycaemia and DM screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
2
9
1
Order By: Relevance
“…The strong influence of whānau/family and household members suggests that there could be important health benefits in engaging them in the education sessions and professional support provided to those with newly diagnosed prediabetes. The dietary information may also be pertinent for the family member(s) given recent studies which found concordance of abnormal glycaemia in couples where one spouse has diabetes . In the current study, and in a UK study in which participants with prediabetes were asked how their prediabetes should be managed , good information and support from a trusted health professional were highly valued.…”
Section: Discussionmentioning
confidence: 84%
“…The strong influence of whānau/family and household members suggests that there could be important health benefits in engaging them in the education sessions and professional support provided to those with newly diagnosed prediabetes. The dietary information may also be pertinent for the family member(s) given recent studies which found concordance of abnormal glycaemia in couples where one spouse has diabetes . In the current study, and in a UK study in which participants with prediabetes were asked how their prediabetes should be managed , good information and support from a trusted health professional were highly valued.…”
Section: Discussionmentioning
confidence: 84%
“…48,49 With a shift from compliance to concordance in diabetes and its complications, spousal concordance is defined by researchers as “shared similarity of habits, behaviours and health statuses among the partners or spouses”. 51,52…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous similar studies investigated the spousal concordance pattern, i.e., the husband-wife association, for lifestyle factors and selected diseases separately. Some reported that there was spousal concordance of cancer [33]; depression [34]; mental disorders [35]; physical frailty [36]; and metabolic components, including overweight/obesity [16,17,34], diabetes [18][19][20]34,37], dysglycemia [17,34], and hypertension [12,16,21,22] among couples. However, one Japanese study revealed that spousal concordance in metabolic components was weak and modest [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that spouses are concordant in several dietary behaviors, such as drinking [10][11][12], alcohol consumption [12,13], fruit and vegetable consumption [14], and the intake of salty food [11]. Furthermore, spousal concordance is also found in MS and its related conditions [15], including being overweight/obesity [16,17], dysglycemia [17], diabetes [18][19][20], hypertension [12,16,21,22], hyperlipidemia [22], coronary heart disease [12,23], and stroke [12]. However, the association between dietary behaviors and metabolic components among spouses is still unclear.…”
Section: Introductionmentioning
confidence: 98%